2003
DOI: 10.1021/jp034392i
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Infrared Spectra and Density Functional Theory Calculations of Manganese and Rhenium Hydrides

Abstract: Laser-ablated Mn and Re atoms react with H 2 upon co-condensation in excess argon and neon and in pure hydrogen to produce metal hydrides. The reaction products are identified through isotopic substitution (D 2 , HD, and H 2 + D 2 ) and density functional theory calculations. The 7 Σ + ground state diatomic MnH is observed at 1493.3 cm -1 in solid neon, 1486.4 cm -1 in hydrogen, and 1477.9 cm -1 in argon. The ReH molecule gives a sharp band at 1985.0 cm -1 in argon, which is suggested to be the 5 Σ + ground st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 68 publications
7
30
1
Order By: Relevance
“…It was found that this is lower in energy than the dissociation limit, ReH 2 ͑ 6 ⌺ g + ͒ +H 2 ͑ 1 ⌺ g + ͒, by 8.8 kcal/mol after dynamic correlation effects are considered by using the MRMP2 method. This is consistent with previous results reported by Andrews et al 27 Since the spinmultiplicities of the lowest states are different, the dissociation reaction of ReH 4 cannot occur without electronic transition from the lowest quartet state to the lowest sextet state. This transition can easily occur because of the strong SOC effects among low-lying states in such heavy metal compounds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that this is lower in energy than the dissociation limit, ReH 2 ͑ 6 ⌺ g + ͒ +H 2 ͑ 1 ⌺ g + ͒, by 8.8 kcal/mol after dynamic correlation effects are considered by using the MRMP2 method. This is consistent with previous results reported by Andrews et al 27 Since the spinmultiplicities of the lowest states are different, the dissociation reaction of ReH 4 cannot occur without electronic transition from the lowest quartet state to the lowest sextet state. This transition can easily occur because of the strong SOC effects among low-lying states in such heavy metal compounds.…”
Section: Discussionsupporting
confidence: 93%
“…This conclusion is consistent with the previous experimental suggestion reported by Wang and Andrews. 27…”
Section: Lowest Quartet Statementioning
confidence: 99%
See 1 more Smart Citation
“…17,33 Molecular MnH or MnH 2 are also observed at lower wavenumbers (1493.3 cm -1 or 1600.8 cm -1 in solid neon). 38 Vibrations of Mn-H in complexes occur at higher frequencies, which range from 1782 cm -1 in HMn(CO) 5 to 1900 cm -1 in HMn(CO) 2 (π-Cp)SiPh 3 . 39,40 Thus, zirconium or manganese hydrides are unlikely to cause the vibrations.…”
Section: Interaction Of Sulfated Zirconia and Mn-promoted Sulfated Zimentioning
confidence: 99%
“…[1,2]. Recent studies include the identification of MnH via cavity ring-down spectroscopy in the laser vaporization of manganese in the presence of CH 4 [3], and the observation of vibrational transitions within the X 7 R + state of matrix isolated MnH [4]. Most recently Gordon et al [5] have recorded and analyzed the Fourier transform infrared emission spectra for the vibration-rotation bands from v = 1 fi 0 to v = 3 fi 2 bands of the X 7 R + state, where MnH was produced in a high-temperature discharge.…”
Section: Introductionmentioning
confidence: 99%